Synthesis and crystallographic structure of nickel(0) carbonyl complex with Bitianp, an atropoisomeric diphosphine - Fusè, Marco; Facchetti, Giorgio; Rimoldi, Isabella; Castellano, Carlo (European Journal of Chemistry, 2019)
The reaction between an atropoisomeric diphosphine, Bitianp and [Ni(CO)4] was achieved by direct condensation in CH3Cl to afford complexes of general formula [Ni(CO)2(Bitianp)]. This compound was characterized by elemental analysis, IR, 1H-, 13C- and 31P-NMR spectroscopies. The structure of nickel complex has been determined by X-ray crystal-lography. Crystal data for C42H28NiO2P2S2 (M = 749.41 g/mol): triclinic, space group P-1 (no. 2), a = 10.539(2) Å, b = 11.811(2) Å, c = 15.994(3) Å, α = 83.93(3)°, β = 88.18(3)°, γ = 65.24(3)°, V = 1797.6(7) Å3, Z = 2, T = 294(2) K, μ(MoKα) = 0.781 mm-1, Dcalc =1.385 g/cm3, 22744 reflections measured (2.56° ≤ 2Θ ≤ 64.726°), 11837 unique (Rint = 0.0157, Rsigma = 0.0215) which were used in all calculations. The final R1 was 0.0360 (I > 2σ(I)) and wR2 was 0.1088 (all data). The coordination sphere of the Ni center is best described as a tetrahedral geometry.